Benefits of Legends for Reading Comprehension, a Study in Madrid, Spain - Palma Campos, Silvia (2023)
This paper aims to present a qualitative analysis of the most important results of a doctoral thesis, in which the perceptions of teachers and students about Central American children's legends in Language and Literature classes in a school in the Community of Madrid are analyzed. Regarding the methodology, the author used a descriptive action-research type, in which it is possible to demonstrate the importance of this narrative genre for linguistic, literary, and sociocultural competencies. Among the techniques and instruments used are: the interview, the questionnaire with open and closed questions, participatory observation, and document analysis. It is determined that legends in primary classrooms have great benefits for students, both for aesthetic enjoyment, learning, and reading comprehension.